Lifestyle Profile Scale for Gravida with Urinary Incontinence: scale development and psychometric testing in Chinese Mainland - Hongyan Wang; Ping Xu; Ping-ping Guo; Xiaojuan Wang; Minna Mao; Suwen Feng (BMJ Open)
Objectives A significant number of women may experience urinary incontinence (UI) during pregnancy. While lifestyle modifications are recommended as important measures for preventing and treating UI, little is known about the lifestyle status of gravida with UI. This study aimed to develop the Lifestyle Profile Scale for Gravida with Urinary Incontinence (LPG-UI) and to evaluate its psychometric properties.Design It was an instrument design study carried out in two stages. In stage 1, a literature review was conducted to generate the initial item pool. Subsequently, a Delphi survey was conducted to obtain expert consensus and reduce the items. In stage 2, further item reduction was performed through item analysis. Then, psychometric properties of the instrument were evaluated, including structural validity, internal consistency, split-half reliability, test–retest reliability and criterion validity.Setting This study was conducted in obstetric clinics of a tertiary maternity hospital in Zhejiang Province, mainland China.Participants A sample of 447 pregnant women with UI were enrolled in stage 2.Results A 24-item, 7-dimension lifestyle profile scale was ultimately obtained. The content validity was satisfactory. The split-half reliability and total-scale Cronbach’s alpha coefficient were 0.890 and 0.819, respectively. The criterion validity was 0.598. The seven-factor model, which accounted for 63.667% of the total item variance, demonstrated a good fit with the data (χ2/df =1.672, root mean square error of approximation=0.053, goodness of fit=0.884).Conclusions The LPG-UI has sufficient validity and reliability for assessing the lifestyle status of pregnant women with UI.